2013
DOI: 10.1175/jtech-d-12-00209.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Temperature Structure Parameter and Sensible Heat Flux over Helsinki from Sonic Anemometry and Scintillometry

Abstract: Two commercial large-aperture scintillometers, Scintec BLS900, were tested on pathlengths of 1840 and 4200 m at about 45–65 m above ground in Helsinki, Finland. From July 2011 through June 2012, large variability in diurnal and annual cycles of both the temperature structure parameter and sensible heat flux were observed. Scintillometer data were compared with data from two eddy-covariance stations. A robust method was developed for the calculation of from raw sonic-anemometer data. In contrast to many earlier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 40 publications
3
22
0
Order By: Relevance
“…The "daytime" behaviour of C 2 T near the surface shows a remarkable repeatability with relative variations of 13-25 %, with two local minima around 0800 and 1600 LST (local standard time = UTC + 8) similar to that observed at mid latitudes (e.g., Beyrich et al 2005;Wood et al 2013). The diurnal maximum observed around 1300 LST is markedly lower than nocturnal C 2 T values.…”
Section: Diurnal Behaviour Of the Meteorological And Turbulent Paramementioning
confidence: 61%
See 1 more Smart Citation
“…The "daytime" behaviour of C 2 T near the surface shows a remarkable repeatability with relative variations of 13-25 %, with two local minima around 0800 and 1600 LST (local standard time = UTC + 8) similar to that observed at mid latitudes (e.g., Beyrich et al 2005;Wood et al 2013). The diurnal maximum observed around 1300 LST is markedly lower than nocturnal C 2 T values.…”
Section: Diurnal Behaviour Of the Meteorological And Turbulent Paramementioning
confidence: 61%
“…Although C 2 T itself is not considered in any ABL model, this characteristic, and especially its variation with height, could be used to estimate more conventional parameters such as the turbulent fluxes or the mixing-layer height. Such attempts were made by Coulter and Wesely (1980), Coulter (1990), Wood et al (2013).…”
Section: -H Behaviour Of the Abl Spatial And Temporal Structurementioning
confidence: 99%
“…The SAS instrument provides fluxes averaged over relatively short paths (up to 250 m), and to obtain fluxes representative of larger areas, a large-aperture scintillometer (LAS) should be used. The LAS instrument has been used in a number of cities, e.g., Marseille (Lagouarde et al 2006), London (Wood et al 2013a), Helsinki (Wood et al 2013b), Łódź (Zieliński et al 2013), Swindon (Ward et al 2014), and Changzou (Zhang and Zhang 2015), London (Crawford et al 2017). More recently, Ward et al (2015a, b) used a system consisting of a LAS intrument and a microwave scintillometer to measure the sensible and latent heat fluxes simultaneously over the city of Swindon in the UK.…”
mentioning
confidence: 99%
“…Scintillometers provide highly reliable heat fluxes and have been successfully applied in turbulent sensible heat-flux measurements in many different environments ranging from natural (e.g., Green et al 1994;De Bruin et al 1995;Beyrich et al 2002Beyrich et al , 2012Meijninger et al 2002;Ezzachar et al 2007;Evans et al 2012) to urban areas (e.g., Kanda et al 2002;Roth et al 2006;Lagouarde et al 2006;Pauscher 2010;Zieliński et al 2013;Wood et al 2013;Ward et al 2014Ward et al , 2015Zhang and Zhang 2015). Large-aperture scintillometers (LAS) allow the estimation of the refractive index structure parameter C 2 n along an optical path of up to several kilometres in length.…”
Section: Introductionmentioning
confidence: 99%
“…Such data are provided by, e.g., the digital surface model, which is based on lidar measurements. However, there is still the question of how these data should be included in the beam-effective height computation, since different authors use different approaches (e.g., Lagouarde et al 2006;Wood et al 2013;Zieliński et al 2013;Ward et al 2014). Lagouarde et al (2006) analyzed the sensitivity of the sensible heat flux to the aerodynamic roughness length z 0 and zero-plane displacement z d , and found that the influence of z 0 is more pronounced than z d (a ±0.5 m error in z 0 can lead to a 10% error in H ).…”
Section: Introductionmentioning
confidence: 99%